PENGELUARAN PEMERINTAH BIDANG KESEHATAN DAN PENURUNAN ANGKA KEMATIAN BAYI DI JAWA BARAT - Wardhana, Adhitya; Kharisma, Bayu; Haekal, M Dzaki Fahd (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022, 2022)
This study aims to analyze the government's role in terms of health expenditure and the availability of health facilities in reducing infant mortality in West Java. This study uses Generalized Least Square (GLS) as the basis for calculations in analyzing the effect of the independent variable on the dependent variable. The scope of the research is 26 regencies/cities in West Java. The dependent variable in this study is infant mortality, while the independent variables, namely the ratio of health expenditures to GRDP, the average length of school and the percentage of the community towards proper sanitation have a negative and significant impact on reducing infant mortality. While the control variable in this study, namely the income variable as a proxy for GDP, has a negative and significant effect on reducing infant mortality.